Pemikiran Ulama Dayah Inshafuddin - Arfah Ibrahim (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2015)
Abstract: Inshafuddin is one of conservative Islamic scholar organizations that still maintains traditional customs, and uphold the values of the kitab kuning (old Islamic books). Nevertheless, they also adapt to modern customs. Thus, Inshafuddin is able to take on a role for social and religious changes in Aceh. The changes are apparent in the thought dynamics of the figures produced by Dayah (conservative Islamic school) of Inshafuddin itself. Among the many are the concepts of thought by promoted by TGK. David Zamzami related to ideologies in Islam, Prof. Dr. Safwan Idris, MA, on BAZIS (Muslim Charitable Donation Board), and TGK. Ismail Jacob about contemporary Islamic jurisprudence. This article aimed to review the thought of these figures from the standpoint of their openness to new ideas.Abstrak: Inshafuddin salah satu organisasi ulama dayah yang masih tetap eksis mempertahankan pola-pola tradisional, dan menjunjung tinggi nilai-nilai kitab kuning. Meskipun demikian, mereka turut serta menyesuaikan diri dengan pola-pola kemoderenan. Dengan demikian Inshafuddin mampu mengambil peran bagi perubahan sosial dan keagamaan di Aceh. Perubahan tersebut terlihat dari dinamika pemikiran yang lahir dari tokoh-tokoh yang ada dalam dayah inshafuddin itu sendiri. Seperti konsep pemikiran Tgk. Daud Zamzami tentang aliran-aliran dalam Islam, Prof. Dr. Safwan Idris, MA, tentang BAZIS (Badan Amil Zakat Infak dan Shadakah), dan Tgk. Ismail Yakub tentang fiqh kontemporer. Artiikel ini dimaksudkan untuk mengulas beberapa pemikiran tokoh tersebut dari sudut pandang keterbukaan mereka terhadap ide-ide baru.